Management of Local Own-Source Revenue in Belu Government: A Phenomenological Study - Taek, Filemon Marselinus; Djamhuri, Ali; Baridwan, Zaki (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020)DO - 10.24843/JIAB.2020.v15.i02.p03, 2020)
This study aims to explore the management of Original Local Government Revenue in the Belu District government with a phenomenological approach, namely an awareness study of the experience of the State Civil Apparatus in managing Original Local Government Revenue and to explain the meaning of the actions taken. The researcher uses the interpretive paradigm understanding method to uncover the aims and objectives of the informants and uses the Husserl phenomenology approach to explain or uncover the phenomenon of experience based on awareness that occurs by individuals, which in this case is the State Civil Apparatus which directly manages Original Local Government Revenue. The results of the study revealed that the informants interpreted the management of Original Local Government Revenue as duties and responsibilities related to the management of Regional Original Revenues including the management of regional taxes whose revenue always fluctuates due to non-compliance of taxpayers. Management of the results of the separated regional wealth always exceeds the target by means of equity participation in BUMD, management of other original authentic regional income by depositing regional cash to the bank and finding other sources of revenue through the auction of assets in the form of vehicles. The management of retribution is constrained due to various obstacles including the lack of adequate facilities. Keywords:   Public sector accounting, original local government revenue, phenomenology, interpretive paradigm, local tax.